Evaluation of speckle-tracking echocardiography in rodent models of cardiovascular disease - Wiro, Aleksi (My University, 2024)
Strain imaging is an ultrasound-based cardiac imaging technique that detects functional abnormalities and ventricular deformation patterns. The aim of this project was to investigate the hypothesis that strain imaging, specifically global longitudinal strain (GLS), is more accurate in detecting early changes in left ventricular function compared to measuring left ventricular ejection fraction (LVEF) by standard echocardiography in rodent models of cardiovascular disease. All data is from previous studies conducted by the research group of Professor Antti Saraste. The study employed rodent models to investigate myocardial infarction (MI), hypertrophic cardiomyopathy (HCM), and dilated cardiomyopathy (DCM). Rats with permanent coronary artery ligation and congenic leptin receptor-deficient rats were used for MI and HCM models, respectively. A mouse model with an LMNA gene mutation was utilized for DCM. Echocardiography, performed with specific ultrasound devices and isoflurane anesthesia, captured cardiac images. Speckle tracking analysis was performed in a blinded fashion with Vevo Strain Software. In this study, we found that left ventricle systolic function measured by either EF or GLS was reduced in a rat model of MI and a mouse model of genetically induced dilated cardiomyopathy, but a rat model of myocardial hypertrophy showed preserved systolic function. We could not show that measuring GLS was better at detecting early cardiac dysfunction compared to standard echocardiography. Although strain imaging has been proposed as a sensitive marker of cardiac dysfunction, we did not find significant differences in the ability of EF and GLS to detect early cardiac dysfunction. Echocardiographic strain appears to be accurate method in detecting cardiac dysfunction in various cardiac diseases that provides similar information to measuring EF by standard echocardiography.
Keywords: strain imaging, myocardial strain, speckle tracking echocardiography, global longitudinal strain